REVISION OF THE K-ISOMER IN W-190(116) - Farrelly, G. F.; Podolyak, Zs.; S.J. Steer; S. Pietri; F.R. Xu; E. Werner-Malento; T. Shizuma; P.H. Regan; D. Rudolph; A.B. Garnsworthy; R. Hoischen; Gorska, M.; et al. (ACTA PHYSICA POLONICA B, 2009)
Gamma rays from the decay of an isomer in W-190(116) have been observed following projectile fragmentation of a 1 GeV per nucleon Pb-208 beam. An earlier experiment indicated decay from a (10(-)) isomer to the ground state rotational band. Improved statistics have enabled gamma coincidence and time-difference measurements to be made which alter the previous interpretation. Blocked BCS calculations have also been used together with reduced hindrance factors to indicate possible values of spin-parity for the isomer.